Precocious puberty in girls attended in a specialized first aid post - Diógenes, Maria Albertina Rocha (2009)
The aim of this work was to evaluate the clinical manifestations of Precocious Puberty (PP) in girls and to investigate their parents’ knowledge concerning the pathology. This a descriptive and documental study, conducted in a specialized first aid post of the public service, in Fortaleza-CE-Brazil, in March 2008. Eighty-two girls from two to twelve years of age, who were using the hormone Gonadorelina, took part in the study. Data collection was held through semi-structured interviews and medical records. The data were analyzed through SPSS, version 15.0, arranged in charts. The thelarche was the first clinical manifestation observed in 42 of the children; concerning the knowledge of parents about precocious puberty, seven did not know how to answer, while 40 said it is when the child leaves childhood earlier, ignoring the real meaning of this pathology. It is necessary that the parents know the signs of precocious puberty to treat their children adequately and to provide them with all the necessary family support.